The Implementation of Community Engagement Models Amongst People With Learning Disabilities in the Context of Health and Social Care: A Systematic Review. - Iqbal, Syka; Ahmed, Farah; Uddin, Inayah; Gilchrist, Katie; Juan, Norha Vera San; Motta, Ana; Fatima, Qanita; Arshad, Saeeda; Vindrola‐Padros, Cecilia (British Journal of Learning Disabilities, 2025)
Background: People with learning disabilities face significant health inequalities, including lower life expectancy and greater physical and mental health challenges. Community engagement approaches are increasingly used in health and social care to address these disparities, yet little is known about their impact. This review explored community engagement models in health and social care for people with learning disabilities. Methods: A search strategy combining 'community engagement' and 'learning disability' was used to identify studies across multiple electronic databases. Studies were included if they provided empirical data on community engagement for people with learning disabilities. Data extraction enabled descriptive analyses, characterising studies in terms of focus, topic area, setting, and factors influencing implementation. Risk of bias was assessed using the MMAT. Findings: Seven papers met the inclusion criteria. Key enablers included embedding approaches within existing services, context‐specific model adaptation, recruiting a coordinator to integrate cross‐sector working, and supportive state policy encouraging community ownership. Barriers included a lack of standardisation, particularly inconsistent definitions of community engagement, varied approaches across services and the absence of clear outcome measures, making it difficult to assess impact. Additional barriers included cross‐sector culture clashes and complex needs prohibiting participation of people with learning disabilities. Conclusion: Community engagement shows promise in addressing health inequalities, but further research is needed to measure its impact on patient outcomes compared to standard care. Findings can guide researchers and policymakers in implementing contextually relevant community engagement approaches. Clinical Trial Registration: N/A. Summary: People with learning disabilities often have a lot of health problems, have shorter lives and do not always get the same level of care as other people.Involving people with learning disabilities in local activities (known as community engagement) can help them feel more included and can improve their health, but we don't know how well this works.This study looked at how community engagement can be organised by those providing care to people with learning disabilities to see what helps or makes it difficult.It is helpful to include community engagement into existing services that think about local needs, having coordinators to link groups, and supportive government policies.Challenges include unclear ways to measure how well community engagement works, different ways organisations organise and prioritise activities and difficulties involving people with multiple needs regularly.Recommendations include longer‐term funding for flexible community engagement activities, to help people with learning disabilities feel included and healthier and more research to find out other ways of improving the health of people with learning disabilities compared to regular care.